Malaysian School Counselor’s Self-Efficacy: The Key Roles of Supervisor Support for Training, Mastery Experience, and Access to Training - Ooi, Pei Boon; Wan Jaafar, Wan Marzuki; Crosling, Glenda (Frontiers in Psychology, 2021)
The concept of self-efficacy has been widely studied and shown to contribute to individuals’ job satisfaction. For counselors, the concept measures their belief in their ability to conduct counseling sessions. However, it is an understudied area. As Bandura states, self-efficacy and its sources should be investigated and measured within its domain, which in this case is school counseling. This study examined the impact on school counselors’ self-efficacy and job satisfaction of the personal and environmental factors: (a) mastery experience, (b) social persuasion, (c) vicarious learning, (d) physiological and affective state, (e) the access to training, and (f) perceived supervisor support of training. The cross-sectional study involved 541 Malaysian secondary school counselors nationwide via a random sampling-distributed questionnaire. Results which were analyzed using PLS-SEM, with importance-performance functionality embedded in it, indicated that mastery experience, access to training, and perceived supervisor support of training explained 45.6% variance in counseling self-efficacy and together with counseling self-efficacy, contributed 13.2% variance in job satisfaction among the school counselors. The importance-performance map analysis revealed supervisor support of training as of greatest importance in shaping counseling self-efficacy. Counseling self-efficacy partially mediated the relationship between mastery experience, access to training, supervisor support toward training, and job satisfaction Arising from this finding is a proposed theoretical framework in which efficacy information (i.e., mastery experience), environmental determinants (i.e., access to training and supervisor support of training) and cognitive determinant (i.e., counseling self-efficacy) corresponded together congruently and lead to higher job satisfaction. Suggestions are also made for training providers, content developers, and policymakers to include these factors in professional development training and continuous education, to sustain the wellbeing of school counselors.